The Mitochondrial Genome Reveals Phylogenetic Relationships and Gene Rearrangement in Brachyura - Kong, Deming; Gan, Zhibin; Li, Xinzheng (Journal of zoological systematics and evolutionary research, 2025)
Brachyura represents the focus of species diversity within Decapoda. However, this diversity increases the difficulty of species identification and obscures the natural phylogenetic relationships. Mitogenomes, with their rich phylogenetic signal and evolutionary informatics, provide critical insights into brachyuran systematics. Here, we present 12 newly sequenced mitogenomes spanning 10 families, which exhibit diverse lengths, ranging from 15,320 to 16,135 bp. All circular genomes except Conchoecetes artificiosus (lacking tRNA‐S2) encode the typical 37 mitochondrial genes. Meanwhile, we identified unique gene order of Pleistacantha cervicornis and provided preliminary speculation on its hypothetical evolutionary history, which involved four gene inversion and translocation events. Phylogenomic reconstruction revealed: (1) Goneplacidae was closely related to Xanthoidea; meanwhile, Tetraliidae and Trapeziidae show divergence, resulting in the polyphyly of Goneplacoidea and Trapezioidea; (2) freshwater crabs were intimately related to thoracotrematan, and we recommended Potamoidea and Gecarcinucoidea should be classified under Thoracotremata; (3) Extensive mitochondrial gene order (MGO) diversity across Brachyura, with lineage‐specific rearrangement patterns serving as phylogenetic markers. Our research offers new insights into the phylogenetic relationships within Brachyura from mitogenome perspective, unraveling the diversity and rearrangement trajectories of MGO in Brachyura.